2020
DOI: 10.32591/coas.ojit.0301.03021p
|View full text |Cite
|
Sign up to set email alerts
|

Using 360˚ Videos for Teaching Volleyball Skills to Primary School Students

Abstract: The study presents the results from a pilot project in which 360˚ videos were utilized for teaching students basic volleyball skills. The target group was thirty-six, eleven-to-twelve years-old primary school students, divided into two groups: the first was taught conventionally and the second using apps in which 360˚ videos were embedded. The project lasted for six two-teaching-hour sessions (three for each method), and data were collected using observation sheets and a questionnaire for recording students’ v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
(82 reference statements)
0
14
0
1
Order By: Relevance
“…AR is widely used, and there are many problems to be solved at the technical level, and there are many applications in teaching. Research by Paraskevaidis and Fokides presented the results of a pilot project using 360 videos to teach students basic volleyball skills [ 5 ]. Turkan et al introduces a new structural analysis pedagogy that combines mobile augmented reality (AR) and interactive 3D visualization techniques [ 6 ].…”
Section: Related Workmentioning
confidence: 99%
“…AR is widely used, and there are many problems to be solved at the technical level, and there are many applications in teaching. Research by Paraskevaidis and Fokides presented the results of a pilot project using 360 videos to teach students basic volleyball skills [ 5 ]. Turkan et al introduces a new structural analysis pedagogy that combines mobile augmented reality (AR) and interactive 3D visualization techniques [ 6 ].…”
Section: Related Workmentioning
confidence: 99%
“…erefore, when teaching high school volleyball drills, teachers should enhance the practice of volleyball tactics for their students. By using multimedia technology in teaching volleyball tactics, you can watch and learn tactics through video materials related to volleyball games, making tactics clearer and more intuitive [13]. At the same time, teachers can also use the demonstration function of multimedia equipment to introduce volleyball tactics and coordination to help students master volleyball tactics and improve their volleyball skills.…”
Section: State Of the Artmentioning
confidence: 99%
“…While the use of video seems to be well established in the field of sport (e.g., Wilson, 2008;Fadde and Zaichkowsky, 2018;Kok et al, 2020;Lee and Chang, 2021), the use of 360 • video still seems to be in its infancy and early experiments in a developing field of research (Araiza-Alba et al, 2021). Paraskevaidis and Fokides (2020) suggested that the potential of 360 • video is still largely unexplored in the research and training fields.…”
Section: • Video Uses In Sports and Physical Education Fieldmentioning
confidence: 99%
“…In recent years, the use of 360 • video has also developed in the field of sports training for multiple purposes: To improve decision-making skills (Panchuk et al, 2018), learn climbing safety procedures (Gänsluckner et al, 2017), increase motivation during practice on fitness devices, such as bicycles or rowing ergometers (Hebbel-Seeger, 2017), and learn motor skills (Paraskevaidis and Fokides, 2020). A total of 360 • videos offer the possibility to "improve the fidelity of training by presenting a realistic, 360 • view of the competitive 10.3389/feduc.2022.898071 environment" (Panchuk et al, 2018, p. 1).…”
Section: • Video Uses In Sports and Physical Education Fieldmentioning
confidence: 99%